2021
DOI: 10.3390/healthcare9030250
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Arabic Coffee and Black Tea in Reducing Halitosis: A Randomized, Double-Blind, Controlled, Crossover Clinical Trial

Abstract: The aim of the study was to objectively evaluate the short-term effect of Arabic coffee and black tea on oral halitosis. This study was a single-center, randomized, double-blind, placebo-controlled, crossover clinical trial on 17 healthy individuals. During the initial visit, pre-treatment breath samples were collected from each subject and analyzed using portable gas chromatography (OralChroma™). Four interventions were evaluated, with Arabic coffee and black tea as the test intervention tools, mouthwash cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Volatile sulphur compounds (VSC), such as hydrogen sulphide, methyl mercaptan or dimethyl sulphide, are responsible for malodour. Zinc ions, by antibacterial effect on VSC-producing bacteria as well as by direct inhibition on some VSC (by converting hydrogen sulphide and methyl mercaptan into non-volatile zinc sulphides), may help in reducing halitosis [ 163 , 164 , 165 ]. They also reduce calculus formation, by crystal growth modification or inhibition [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile sulphur compounds (VSC), such as hydrogen sulphide, methyl mercaptan or dimethyl sulphide, are responsible for malodour. Zinc ions, by antibacterial effect on VSC-producing bacteria as well as by direct inhibition on some VSC (by converting hydrogen sulphide and methyl mercaptan into non-volatile zinc sulphides), may help in reducing halitosis [ 163 , 164 , 165 ]. They also reduce calculus formation, by crystal growth modification or inhibition [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be that we were assessing self-perceived halitosis and smokers are less likely to report it owing to reduced olfactory sensitivity 16 . In the present study, 22% population reported consuming >2 cups of tea/coffee in a day, and this population had a higher frequency of selfperceived halitosis (p=0.018) although an in vitro study and a crossover randomised controlled trial (RCT) reported to have reduced volatile sulphur compounds (VSCs) with coffee 17,18 .…”
Section: Discussionmentioning
confidence: 52%
“…In the present study, individuals consuming both tea and coffee are 3.33 times more likely to have SPH as compared to those consuming no beverages. Evidence linking halitosis to tea and coffee consumption is scarce, although it might be beneficial for oral health owing to their antimicrobial properties [ 26 ]. Tobacco smoke contains VSCs, which is a type of malodorant.…”
Section: Discussionmentioning
confidence: 99%